2014
DOI: 10.11564/28-0-557
|View full text |Cite
|
Sign up to set email alerts
|

Male Circumcision and Risky Sexual Behavior in Zimbabwe: Evidence from the 2010-11 Zimbabwe Demographic and Health Survey

Abstract: In 2009, Zimbabwe adopted voluntary medical male circumcision (VMMC)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 9 publications
1
8
0
Order By: Relevance
“…The methodology used in this study is similar to the one used in an earlier study which focused on the association between circumcision status and risky sexual behaviour [ 12 ]. The study relied on data on men between the ages of 15 and 54 years obtained from the Zimbabwe Demographic and Health Survey (ZDHS) of 2010–11.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The methodology used in this study is similar to the one used in an earlier study which focused on the association between circumcision status and risky sexual behaviour [ 12 ]. The study relied on data on men between the ages of 15 and 54 years obtained from the Zimbabwe Demographic and Health Survey (ZDHS) of 2010–11.…”
Section: Methodsmentioning
confidence: 99%
“…Subsequent studies have shown a high level of knowledge of VMMC among women and men in Zimbabwe [ 6 , 9 ]. Studies on circumcision and behavioural disinhibition among circumcised men in Kenya, Malawi and Zimbabwe have also allayed fears that circumcised men engage in risky sexual behaviour [ 10 - 12 ]. However, in Uganda, it was found that circumcised men engaged in riskier sex behaviour compared to uncircumcised men although their HIV prevalence rate is lower [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Zimbabwe (21). They all found no significant differences in risky sexual engagement between circumcised and uncircumcised men following circumcision.…”
Section: Introductionmentioning
confidence: 90%
“…In the era before the RCT results were known, men may thus not have changed their sexual behaviors following circumcision. Those studies that were conducted in the era after publication of the RCT results mainly used cross-sectional surveys 12 , 13 , 20 or qualitative interviews 14 , 15 and thus allowed only relatively weak inference on causal effects. One study carried out in the post-RCT era from the Rakai district of Uganda used longitudinal data to identify incident circumcision and to relate this exposure information to sexual behavior.…”
Section: Introductionmentioning
confidence: 99%